UNDERSTANDING THE IMPLICATION OF OCCUPATIONAL DISTRIBUTION ON INCOME INEQUALITY: EVIDENCE FROM NADOWLI-KALEO DISTRICT, GHANA - Agbenyo, F.; Ngben, J. M.; Alhassan, S. (UDS International Journal of Development, 2017)
The paper seeks to establish the implication of occupational distribution on income inequality. Data was collected from five independent sub-groups, two from the formal and the other two from the informal sectors with a fifth sample generated from these four samples. Lorenz curves and Gini coefficients were used to measure income inequality. The results show that though formal sector income sub-groups generated higher incomes they produced lower inequalities than the informal sector income sub-groups which induced lower incomes due to salary harmonization using the single spine salary structure policy introduced in 2010. The paper also reveals that even though the Lorenz curve and Gini index are very useful in establishing intra sub-group inequalities their application to inter sub-group inequalities for comparative purposes is problematic since both tools are unable to deal with variations in income levels across income sub-groups. The bootstrap confidence intervals were constructed to deal with the statistical testability enigma of the Gini index. The results show that the empirical statistics and by extension Gini coefficients were significant at 95% confidence interval. The paper recommends that policies targeted at solving the inequality puzzle in low income countries should always be accompanied with growth generating policies for the expansion and sustained poverty and income inequality reduction. Keywords: Income inequality, Poverty, Lorenz Curve, Gini coefficient, Nadowli-Kaleo District